1999
DOI: 10.1136/jcp.52.2.118
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the histological criteria used to diagnose infection in hip revision arthroplasty tissues.

Abstract: Aim-To characterise the number and nature of the inflammatory cells seen in cases of septic or aseptic loosening of hip arthroplasty, and to establish reliable histological criteria to distinguish between these two conditions. Methods-Histological examination of paraYn sections of periprosthetic tissues (pseudocapsule, femoral and acetabular pseudomembranes) of 523 cases of aseptic loosening and 79 cases of microbiology culture proven septic loosening. The cellular composition of the inflammatory cell infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
0
19

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 17 publications
3
102
0
19
Order By: Relevance
“…We conclude that histopathological analysis of PMN infiltration in periprosthetic tissue is the best method to distinguish between aseptic and septic loosening of hip prostheses. The usefulness of PMN infiltration is supported by the work of Pandey et al (1999) and Musso et al (2003). The latter authors recommended histology for all suspected cases of total joint infections.…”
Section: Discussionmentioning
confidence: 93%
“…We conclude that histopathological analysis of PMN infiltration in periprosthetic tissue is the best method to distinguish between aseptic and septic loosening of hip prostheses. The usefulness of PMN infiltration is supported by the work of Pandey et al (1999) and Musso et al (2003). The latter authors recommended histology for all suspected cases of total joint infections.…”
Section: Discussionmentioning
confidence: 93%
“…Cultures were discontinued and considered negative if no growth was reported after 14 days according to previous studies [24,45,49]. Cultivation of tissue samples was performed essentially as previously described [4,24,42,49,52]. Media were checked daily for bacterial growth.…”
Section: Methodsmentioning
confidence: 99%
“…Although the Gram stain has been commonly used to help diagnose periprosthetic infections associated with total hip arthroplasty, various authors have observed the sensitivity of the test is extremely low, with only a single report of a sensitivity greater than 20% [1,2,8,13,17,21]. Recent reports of the effectiveness of Gram staining in diagnosing periprosthetic infection continue to report low sensitivities, and suggest this test does little to aid the surgeon in making a definitive infection diagnosis [2,8,9,23].…”
Section: Introductionmentioning
confidence: 99%